Qualitative assessment of municipal solid waste compost by indexing method - Papiya Mandal; M. K. Chaturvedi; J. K. Bassin; A. N. Vaidya; R. K. Gupta (International Journal of Recycling of Organic Waste in Agriculture)
Background A study was carried out to classify municipal solid waste (MSW) compost produced in Delhi, India for their marketability and use in different area with respect to physico-chemical properties, fertilizing and heavy metal polluting potentials. Results The pH of the compost was slightly alkaline (8.4 ± 0.02) and C:N ratio (9.46 ± 0.91) was low as compared to Fertilizer Control Order (FCO) Standard, Government of India, 1985. Sample analysis was carried out using standard methods. The concentrations of some selected heavy metals, e.g., Zn, Cd and Ni were within the permissible limit of FCO standard. However, the concentrations of Cu, Pb and Cr exceeded (66.7 %) the permissible limit of FCO standard. Further, the compost was characterized to know the fertilizing potential and its potential to contaminate the soil. Fertilizing index (FI) was calculated from the values of TOC, TN, TP, TK and C:N ratio and clean index (CI) was also calculated using heavy metal concentrations. FI value of compost was varied from 4.47 to 4.60, whereas CI value of compost was varied from 2.33 to 2.87, respectively. Conclusions The study results indicated that majority of MSW compost produced in Delhi failed to achieve quality control guidelines of FCO standard. The compost has fertilizing potential, however, certain risk to the environment. Hence, the prepared compost in Delhi was not suitable for its intended purpose. Post-treatment of compost is required to improve the quality of compost, which can be utilized for agricultural purposes.